A 45-cm monster - Schwartz, Martín Alejandro (2019)
In June 2014, the Faculty of Astronomical and Geophysical Sciences of the National University of La Plata, Argentina, received a telescope as a donation from the family of Dr. Rafael Montemayor. This instrument was a personal project of the professor and researcher of the Balseiro Institute (Bariloche, Argentina), in which he worked during the last 17 years of his life, completing 80% of the mechanical aspects. The mount with a C-ring type design is very robust, the telescope has a parabolic primary mirror (f = 2027 mm and D = 457.2 mm) prepared to operate in Newtonian focus. Our goal is to complete the assembly and automation of the telescope, which will be used remotely for scientific, educational and outreach purposes. The development of the pointing electronics and control software are complete and have been tested with Meade telescopes.